Surfactant‐Free Aqueous Synthesis of Pure Single‐Crystalline SnSe Nanosheet Clusters as Anode for High Energy‐ and Power‐Density Sodium‐Ion Batteries. Issue 4 (22nd November 2016) - Yuan, Shuang; Zhu, Yun‐Hai; Li, Wang; Wang, Sai; Xu, Dan; Li, Lin; Zhang, Yu; Zhang, Xin‐Bo
Abstract : SnSe with 3D hierarchical nanostructure composed of interconnected single‐crystal SnSe nanosheets is synthesized via a fast and effective strategy. Unexpectedly, when used as the anode material for Na‐ion batteries (NIBs), the SnSe exhibits a high capacity (738 mA h g −1 ), superior rate capability (40 A g −1 ), and high energy density in a full cell. These results provide the possibility of SnSe use as NIBs anodes.